Exploring the financial and psychological factors influencing Female driving in Dammam Metropolitan Area, KSA - Nawaf Mohamed Alshabibi (Social Sciences and Humanities Open)
Women comprise half of the global population and their driving demand, patterns, behavior, and path choices differ from those of men drivers. The recent lifting of the ban on women driving in the Kingdom of Saudi Arabia (KSA) has significant implications for transportation networks, safety, and capacity. To mitigate potential negative impacts, it is crucial to understand the financial and psychological factors that influence women driving behavior. This paper-based survey study was conducted among 349 women participants in Dammam Metropolitan Area (DMA) to assess their attitudes towards driving private vehicles the target was 350 women but 1 woman refused to participate. The results show that two-thirds of the women participants would like to drive a private vehicle, but one-third cannot or do not want to for reasons related to financial ability and psychological desire. To promote women driving in the KSA, policy interventions could focus on improving the affordability of private vehicles, increasing the availability of women driving instructors, raising community awareness, and providing information technology-based transportation services.